PENGARUH KUALITAS PELAYANAN (ASPEK FISIK, KEANDALAN, INTERAKSI PRIBADI, PEMECAHAN MASALAH, DAN KEBIJAKAN) TERHADAP KEPUASAN KONSUMEN MIROTA KAMPUS DI YOGYAKARTA - Suryono, Wisnu; Setyono, Hendro (Jurnal Fokus Manajemen Bisnis, 2014)
This study aims to determine whether that service quality dimension in the physical aspects, reliability, personal interaction, problem solving and policy affects customer satisfaction supermarket Mirota Campus in Yogyakarta and analyze the most dominant factor in influencing customer satisfaction Supermarket Mirota Campus. The population in this study are consumers/customers supermarket Mirota Campus. Samples taken as many as 300 respondents by using incidental sampling and purposive sampling. Based on the analysis of statistical data, indicators in this study are valid and are reliable variables. The sequence individually from each of the most influential variables is the variable with the problem-solving test value t for 5.608, the personal interaction with the t test value of 4.826, followed by policy variables with a value of 3.845 t test and physical aspects variables with the value of the t test for 2.595, whereas the lowest variable that is variable with a value of t-test reliability sebesar 1.886.